Hubungan Tingkat Pengetahuan Terhadap Perilaku Vaksinasi Covid-19 Pada Masyarakat Kota Samarinda - Sinta Ratna Dewi (JURNAL FARMASI DAN MAKANAN, 2022)
Outbreak is corona virus disease or what is often called COVID-19 is a problem in the world and also in Indonesia. In addition to the implementation of a good understanding and knowledge of all elements including society, in addition, one of the factors that influence a person's behavior is the level of knowledge. This study aims to determine the relationship between the level of knowledge and covid-19 vaccination behavior in the people of Samarinda City. This study used quantitative research with a cross-sectional design where the number of samples in this study was 130 samples obtained from direct interviews and filling out questionnaires. The data analysis in this study was to use the Pearson correlation test. Based on the results obtained, it shows that out of a total of 130 respondents, a sig value (2-tailed) of 0.000 <0.05 is known so that it can be said that there is a significant relationship between 2 variables, namely knowledge and perception, besides that, a correlation coefficient of 0.346 is obtained, which means that the level of strength or correlation of the relationship between 2 variables is weak. Knowledge is one of the factors that influence a person's behavior, so the higher the knowledge about vaccines, the higher the public's desire to vaccinate against COVID-19.